2008
DOI: 10.1016/j.ejcts.2008.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of self-expanding venous cannulas for cardiopulmonary bypass: benefits and pitfalls in 100 consecutive cases☆

Abstract: Full or more than target flow was achieved in 97% of the patients studied undergoing CPB with self-expanding venous cannulas and gravity drainage. Remote venous cannulation with self-expanding cannulas provides similar flows as central cannulation. Augmentation of venous return is no longer necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Satisfactory full flow CPB can be obtained even in the case of obese patients, frequently without vacuum assisted drainage, and a comfortable surgical view can be obtained, even using a ministernotomy approach. Our experience also confirms recent findings from von Segesser et al [6] who showed feasibility of full-flow CPB using a subclavian venous drainage in 7 patients. Using their original self-expanding venous cannula, which could be an excellent option for axillo-axillary CPB, they achieved 111% of calculated target pump flow, without reporting any major vascular complications.…”
Section: Discussionsupporting
confidence: 94%
“…Satisfactory full flow CPB can be obtained even in the case of obese patients, frequently without vacuum assisted drainage, and a comfortable surgical view can be obtained, even using a ministernotomy approach. Our experience also confirms recent findings from von Segesser et al [6] who showed feasibility of full-flow CPB using a subclavian venous drainage in 7 patients. Using their original self-expanding venous cannula, which could be an excellent option for axillo-axillary CPB, they achieved 111% of calculated target pump flow, without reporting any major vascular complications.…”
Section: Discussionsupporting
confidence: 94%
“…As reported previously, the selfexpanding venous cannulas [7][8][9][10] can be stretched and collapsed with a hollow mandrel, inserted into the venous vasculature over a guide wire through an access orifice similar to the size of the peripheral vein or even smaller [11] and expanded to its nominal diameter of 36 F within the vena cava (typical diameter in adults is >20 mm or 60 F) or to the available luminal width of the access vessel (typical diameter of the femoral vein is 8 mm or 24 F). Already at the iliac level, the vein diameter increases, and, therefore, the narrow segment of a well-positioned self-expanding cannula is relatively short.…”
Section: Discussionmentioning
confidence: 95%
“…We have termed this phenomenon temporary caval stenting as it allows the cannulated vein to stay open and prevents it from collapsing [15]. In contrast to cardiopulmonary bypass for open heart surgery, where gravity drainage is sufficient for achieving the target flow in conjunction with the selfexpanding cannula [10], temporary caval stenting is even more helpful, when higher negative pressures in the venous cannula can be expected similar to augmentation using centrifugal pumps or vacuum. The term 'temporary' refers here to the fact that the caval stenting is reversible as the self-expanding cannula can be re-collapsed by simple traction and therefore easily removed at the end of the extracorporeal circulation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations